2022
DOI: 10.3389/fphar.2022.904420
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib Alleviates Experimental Colitis by Inhibiting CEBPB/PCK1 and CEBPB/EFNA1 Pathways

Abstract: The super-enhancer, a cluster of enhancers with strong transcriptional activity, has become one of the most interesting topics in recent years. This study aimed to investigate pathogenic super-enhancer–driven genes in IBD and screen therapeutic drugs based on the results. In this study, through the analysis of differentially expressed genes in colitis patients from the GEO database and the analysis of the super-enhancer–associated database, we found that the super-enhancer pathogenic genes PCK1 and EFNA1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…MMP25 can degrade ECM proteins and promote embryonic growth and development, ovulation, uterine degeneration, and wound healing [26]. CEBPB participates in tumorigenesis and apoptosis, proliferation and differentiation, and systemic in ammatory response by regulating the gene transcription of target cells [27]. CRISPLD2 is a glucocorticoid responsive gene, regulating immune response [28].…”
Section: Discussionmentioning
confidence: 99%
“…MMP25 can degrade ECM proteins and promote embryonic growth and development, ovulation, uterine degeneration, and wound healing [26]. CEBPB participates in tumorigenesis and apoptosis, proliferation and differentiation, and systemic in ammatory response by regulating the gene transcription of target cells [27]. CRISPLD2 is a glucocorticoid responsive gene, regulating immune response [28].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been observed that the down-regulation of EFNA1 expression exerts inhibitory effects on the three-dimensional growth of HT29 colon cancer cells [ 31 ]. Previous studies have also reported that exhibits a therapeutic effect in experimental colitis by inhibiting the CEBPB/PCK1 and CEBPB/EFNA1 pathways, which are associated with the PI3K-Akt and P38 MAPK pathways [ 32 ]. CRNG disruption and overexpression, in conjunction with KITLG, have been observed to interact and engage in viral and pathogenic infections in PK-15 cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our model, PCK1 pathway is activated by the IL6-IL6R interaction in the liver, which is feeds back to the lung pathogenesis of IPF via KNG1-BDKRB1 pathway. Recently, nintedanib, one of the two FDA-approved IPF therapeutics, is shown to attenuate experimental colitis via inhibiting the PCK1 pathway 43 . This study suggests that a part of the therapeutic effect of nintedanib on IPF is via the inhibition of the PCK1 pathway.…”
Section: The Inter-organ Mechanism Of Ipfmentioning
confidence: 99%